Numerical Study of Topology Optimization of Jacket Platform: A Review - Megat Iskandar, Megat Amirul Adli (IRC, 2020)
Topology optimization of Offshore Platform is a mathematical method that optimizes material layout of the offshore platform within a given design space, for a given set of loads, boundary conditions and constraints with the goal of maximizing the performance of the platform and to optimize the capital cost of the platform. In this paper, the optimization of the offshore platform is compared between researcher’s paper article to know into details of the principle used and the methodology for the optimization. The highlight of the optimization is on the structural of the offshore platform and the topside of the platform. Aside for those, the technology being used would also affect on the optimization for the platform. The industry has been imposing new technology and better design as time goes by. However, this latest upgrade would still be based on the previous research that have been done on the similar subject. Thus, by reviewing several research papers, we could obtain the findings that could be used to propose numerically for the topology optimization process.